HYDROTROPIC SOLUBILIZATION AND LINEARITY PROFILE OF PAZOPANIB - KARAJGI, SANTOSH; POTADAR, SHRIPAD (International Journal of Current Pharmaceutical Research, 2020)
Objective: A study on the hydrotropic solubility and linearity profile of Pazopanib was carried out by using Niacinamide as the solubilizing agent as Pazopanib is poorly soluble in water. Methods: Pazopanib was freely soluble in water when 2.8M Niacinamide was used as a solubilizing agent. Pazopanib shows an absorption maximum at 282 nm in First derivative mode of measurement using Shimazdu UV Spectrophotometer 1800 spectronic model. Results: At the absorption maximum of 282 nm, Pazopanib shows a linear response in the range of 5μg/ml to 15μg/ml concentration. Conclusion: The present study is useful for the aqueous solubilization and quantitative determination of Pazopanib in bulk drug and in pharmaceutical formulations thus avoiding toxic solvents.